(untitled) (Confluenţe Bibliologice, 2019)
The author, studying various historical sources, reports on the diﬃculties that arose in the society after the Great Union of 1918: ”It was diﬃcult to win the sincere attachment of the Romanian Basarabian to the Romanian state. He was out of a yoke, and he was afraid of overtaking another. The Romanian administrative bodies have often neglected these aspects.It has neglected to observe the laws of the country and even a certain fear of the administration. This state was also due to the conduct of oﬃcials in the administration who did not always meet the requirements, even serious violations being recorded “.